Prevalence of asthma and related symptoms among schoolchildren in Dezful city, Southwestern Iran - Mohammad Nejadhosseini; Abdolhussein Shakurnia; Abdolkarim Sheikhi; Farhad Abolnezhadian (Jorjani Biomedicine Journal)
Background: Asthma is a chronic respiratory disease and a major public health problem globally. This study aimed to determine the prevalence of asthma and related symptoms in schoolchildren in Dezful city, southwest Iran. Methods: In this cross-sectional descriptive analytical study, the prevalence of asthma symptoms was measured using a randomized cluster sampling method among 2,978 schoolchildren aged 6-14 years. A validated questionnaire from the International Study of Asthma and Allergies in Childhood (ISAAC) was used from January to February 2020. The chi-square test was used to determine the relationship between variables, which were expressed as percentages, with a p‐value <0.05 considered statistically significant. Results: The overall prevalence of asthma was 4.7% (CI=3.98 - 5.54), significantly higher among 13-14-year-olds compared to the 6-7-year-old age group (6.4% vs. 3.1%, p<0.001) and in males versus females (6.9% vs. 2.5%, p<0.001). The total prevalence of wheezing in the last year, the main symptom of asthma, was 7.2% (CI=6.31 - 8.20), significantly higher among 13-14-year-olds (8.4% vs. 6.1%, p<0.009) and male schoolchildren (9.6% vs. 4.7%, p<0.001). Conclusion: According to our findings, and compared to the previous ISAAC study in Iran, the prevalence of asthma symptoms was relatively low among Dezful schoolchildren. Further epidemiological studies are needed to investigate factors affecting this disease, such as indoor and outdoor environments, as well as their effects on gene expression over time.